Electrochemical Functionalization of Imidazopyridine and Indazole: An Overview. Issue 22 (12th October 2021) - Ghosh, Debashis; Ghosh, Sumit; Hajra, Alakananda
Abstract: Electrochemical synthesis offers a mild, simple, and efficient tool for the preparation of interesting and useful molecules, thus eluding severe chemical oxidizing and reducing agents used in conventional synthetic methods. In particular, electrochemical C−H activation is expected to play an important role in the direct functionalization of heterocyclic compounds. Over the past few decades, the research interest in imidazopyridine and indazole has increased significantly due to their multipurpose uses in medicinal and industrial chemistry. Therefore, structural modification of these heterocycles using electro‐oxidation has become one of the important research topics among synthetic organic chemistry in recent time. This review provides a comprehensive discussion of electrochemical functionalization of indazoles and imidazopyridines published so far. A summary of the current challenges and the future direction for the development of efficient and green electrochemical methods for functionalization of these heterocycles is also presented. Abstract :